Cephalopods in the food of Weddell seals from the Admiralty Bay (King George Island, South Shetland Islands) - Lipinski, Marek; Woyciechowski, Michal (Polish Academy of Sciences, 1981)
It has been a long known fact that Weddell seals eat cephalopods. Bertram (1940) has found that Weddell seals from Graham Land fed equally on fish and cephalopods. Deaborn (1965) has observed that Weddell seals from the surroundings of McMudro Sound fed mainly on fish (97% of stomachs with food). Cephalopods were found in 14% of stomachs. These were octopuses from the subfamily Eledoninae, not identified any further. In one of the stomachs there were 7 octopuses and 42 beaks. Wilton (1908) and Pohle (1927) have pointed out the significance of squids (Teuthoidea) in the food of Weddell seals.